Media Pembelajaran Berbantuan Sparkol Materi Program Linier Metode Simpleks - indriyani, Indriyani; Putra, Fredi Ganda (Universitas Islam Negeri Raden Intan Lampung, 2018)
Mathematics is a means of communication science about patterns that are useful to practice thinking logically, critically, creative and innovative. The importance of mathematics in education is inversely related to the interest of students, because mathematics is considered to be difficult and tedious, it is necessary for the innovation in learning so that math seems easy and interesting, namely one of them with developing a learning media in the form of a video by using the app Sparkol's video scribe. The purpose of this research is learning media math using software Sparkol Video scribe on the main discussion of linear program simplex method, as well as test the feasibility and know the response of students to the media. This study uses a model ADDIE which includes 5 steps, namely: analysis (analyze), planning (design), development (development), implementation (implementation), and evaluation (evaluation). The feasibility of learning media obtained from the results of the validation by media experts and matter experts with the category and the attractiveness of the video data obtained from a questionnaire filled by the students include small class and large class and qualitatively qualified interesting.